Anxiety disorders and anxiety symptoms in pregnant women in Iceland and how they fare from pregnancy to postpartum - Inga Lilja Hilmarsdóttir 2001-; Steinunn Vala Arnarsdóttir 1999- (2023)
Studies have shown that anxiety during pregnancy can have negative outcomes for both mother and child, therefore, screening for anxiety in pregnant women is important. The main purpose of this study was to examine how pregnant women with anxiety disorders and anxiety symptoms fared postpartum. The participants were 2523 pregnant women in Iceland, in the age range 17 to 47 years. All participants answered two screening lists, EPDS and DASS, at least at one point during pregnancy and/or postpartum. Those screened positive, along with a control group, were asked to participate in a diagnostic interview during pregnancy and/or postpartum. Of the 578 women that attended a diagnostic interview during pregnancy, 182 (31.5%), were diagnosed with an anxiety disorder, the most prevalent being generalized anxiety disorder. The results showed a significant relationship between receiving an anxiety disorder during pregnancy and outcomes postpartum, such as showing anxiety symptoms, receiving an anxiety disorder diagnosis, showing depressive symptoms, and receiving a major depressive disorder diagnosis postpartum. In addition, there was a significant relationship between showing anxiety symptoms during pregnancy and showing anxiety symptoms postpartum. In conclusion, the results indicated that women with anxiety during pregnancy were likely to suffer from anxiety and/or depression postpartum. Keywords: pregnancy, postpartum, anxiety disorders, depression, and diagnostic interview Rannsóknir hafa sýnt að kvíði á meðgöngu getur haft neikvæðar afleiðingar fyrir bæði móður og barn og þess vegna er mikilvægt að skima fyrir kvíða hjá þunguðum konum. Megintilgangur þessarar rannsóknar var að kanna hvernig þunguðum konum með kvíðaraskanir og kvíðaeinkenni farnaðist eftir fæðingu. Þátttakendur voru 2523 þungaðar konur á Íslandi á aldursbilinu 17 til 47 ára. Allir þátttakendur svöruðu tveimur skimunarlistum, EPDS og DASS, að minnsta kosti einu sinni á meðgöngu og/eða eftir fæðingu. Þær sem skimuðust jákvæðar, ásamt samanburðarhópi, ...